2023
DOI: 10.1111/roiw.12652
|View full text |Cite
|
Sign up to set email alerts
|

Warning: Some transaction prices can be detrimental to your house price index

Abstract: There is a broad consensus in international statistical organizations such as Eurostat and the International Monetary Fund that house price indices (HPIs) should be constructed using transaction data. We show here how transaction data for new‐built properties can undermine the timeliness of hedonic HPIs when new‐built properties are pre‐sold during the planning or building stage, but entered into deed books only once the projects are completed. As a consequence, HPIs for new‐builds will include stale transacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
(65 reference statements)
0
3
0
Order By: Relevance
“…Using data for both markets together may cause some bias, which may appear according to lag in the primary market. Recent research indicates that data from the primary real estate market should be analyzed with a lag of 2 quarters due to the length of the investment process in this market (Hill et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Using data for both markets together may cause some bias, which may appear according to lag in the primary market. Recent research indicates that data from the primary real estate market should be analyzed with a lag of 2 quarters due to the length of the investment process in this market (Hill et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Islam et al [20] found that, in general, the presence of a garage increases the rental price of a home by 15% and, analyzing by planned and unplanned areas, they found that the presence of garages in planned areas has a greater impact than in unplanned areas. The study conducted by Hill et al [47], using hedonic modeling, found a positive impact of structural attributes, such as area and the presence of a garage, for both new and existing apartments in the cities of Warsaw and Pozna ń.…”
Section: Structural Attributesmentioning
confidence: 99%
“…Nonetheless, they agree that using offer prices in forecasting models improves accuracy. Moreover, in the case of new builds listings can provide more reliable information on the housing market than transactions (Hill et al, 2023).…”
Section: Datamentioning
confidence: 99%